Effect Of Jala Neti In The Management Of Vataja Pratishyaya W.S.R. To Allergic Rhinitis - Thakur, Priyanka; Bhardwaj, Vijayant; Sharma, Satish; Gupta, Rajika; Sharma, Priya (International Research Journal of Ayurveda & Yoga, 2020)
Pratishyaya is a condition of continuous nasal discharge, Vata pradhan disease occur due to accumulation of Doshas in Uttamang. According to signs and symptoms of Vataja Pratishyaya it can be correlated with Allergic Rhinitis was selected for the study. The present study was done on 10 patients of Vataja Pratishyaya in single group. Jala Neti (NASOWASH as neti patra, a modernized form of jala neti) was done. The signs and symptoms were studied before and after treatment. Results of study showed moderate improvement in 80% of patients and mild improvement in 20% patients.